PRE-SERVICE ENGLISH TEACHERS’ BARRIERS IN PROMOTING STUDENTS COMMUNICATION SKILL IN EFL CLASSROOM - Eka Nurhidayat (Journal of English Language Learning, 2021)
The purpose of this study was to ascertain the pre-service English teacher's strategy for enhancing students' communication skills in the EFL classroom, the obstacles students encountered when the teacher implemented strategies for enhancing students' communication skills in the EFL classroom, and the implications for students when the teacher implemented strategies for enhancing students' communication skills in the EFL classroom. The method used in this study is descriptive qualitative, with six students and two teachers serving as research participants. The data collection technique used in this study is interviewing. The findings from the three research questions indicate that pre-service English teachers use role playing, presentation, group work, and English debate to improve their communication skills. Students face difficulties when their teacher uses these strategies because they lack confidence when speaking, lack of vocabulary mastery, their environment is non-English speaking, and their learning style is non-English speaking. Students perceive the teacher as a facilitator who assists them in improving their communication skills in the EFL class, and thus the teacher's implication is positive in this case.